Treponema pallidum infection in asymptomatic persons: A puzzling scenario in the Canary Islands (Spain) (2001–2020) - Jose Luis Pérez-Arellano; Araceli Hernández Betancor; Oscar Sanz Peláez; Jose Curbelo; Michele Hernández Cabrera; Elena Pisos Álamo; Nieves Jaén Sánchez; Laura Suárez Hormiga; Carmen Lavilla Salgado; Laura López Delgado; Sandra González Linares; Cristina Carranza-Rodríguez (PLoS ONE, 2025)
Background and objectives Syphilis is an infectious disease caused by T. pallidum subsp. Pallidum . In high-income countries the main mode of transmission is sexual. Approximately half of infected patients are asymptomatic, which does not exclude the possibility of transmission. The aim of this study was to evaluate syphilis seroprevalence among asymptomatic persons in Gran Canaria (Canary Islands, Spain). Patients and methods Three different groups were studied from 2001 to 2020 : i) a “blood donor” sample of 948,869 voluntary blood donations as a proxy of health population.; ii) undocumented African immigrants, including 1,873 recent arrivals in Gran Canaria; and iii) people living with HIV (PLWH), a group of 1,690 patients followed by our team. The evaluation included both treponemal and reaginic tests. Results i) among blood donors, the mean seroprevalence of positive treponemal tests was 0.25% (95% CI: 0.19–0.31). Non-treponemal test positivity (RPR) ranged from 0.05 to 0.06% with titers ≤ 1:4 in all cases; ii) thirty-four of 641 undocumented African migrants (5.30%; 95% CI: 3.82–7.32%) had a confirmed positive treponemal test but only 4 had a positive RPR, with titers ranging from 1:1–1:4; iii) 46.51% (95% CI: 44.14–48.89) of PLWH patients had a confirmed positive treponemal test. For factors related to HIV-syphilis coinfection, multivariate analysis clearly showed the association with male sex and the MSM risk category. However, the results of this series call into question the overall role of immigration in the seroprevalence of syphilis among PLWH in our setting. Active syphilis (RPR > 1:8) was found in 20.10% of PLWH. Conclusions In summary, syphilis is a re-emerging infection, and asymptomatic persons constitute a group that facilitates its transmission and spread. In our setting, seroprevalence was lowest in blood donors, higher in recently arrived African migrants, and highest in PLWH, especially MSM. The presence of active syphilis however is mainly restricted to MSM. This information is of relevance for the design of syphilis control strategies.